The Impact of Thyme and Rosemary on Prevention of Osteoporosis in Rats - Amr S. Elbahnasawy; E. R. Valeeva; Eman M. El-Sayed; I. I. Rakhimov (Journal of Nutrition and Metabolism)
Osteoporosis poses an important public health problem which affects millions of people worldwide. There is a direct link between calcium deficiency in diet and induction of osteoporosis and bone loss. The current study was conducted to evaluate the protective effect of thyme (Thymus vulgaris L.) and rosemary (Rosmarinus officinalis L.) against osteoporosis in rats with low calcium intake. Essential oils of rosemary and thyme were analyzed. The experiment was carried out on growing male Sprague–Dawley rats; the experimental animals were divided into 5 groups: 1, control negative was fed standard balanced diet; 2, control positive was fed balanced diet with low calcium level (L Ca) (Ca 0.1% w/w); 3, (L Ca) + thyme powder (5% w/w); 4, (L Ca) + rosemary powder (5% w/w); 5, (L Ca) + orally administration with CaCO3 (27 mg/kg body weight). Blood samples were collected for different biochemical analyses in plasma (calcium (Ca), phosphorus (P), magnesium (Mg), tumor necrosis factor-alpha (TNF-α), C-reactive protein (CRP), malondialdehyde (MDA), parathyroid hormone (PTH), C-terminal telopeptide (CTX), and 1,25-(OH)2-vitamin D3). Femur mass, length, and bone mineral density (BMD) were recorded, and histopathological studies for femurs were examined. Low-calcium diet induced osteoporotic changes in positive control rats (decrease in Ca, vitamin D3, and BMD and increase in CTX, PTH, TNF-α, CRP, and MDA). Supplementation with thyme and rosemary inhibited significantly the development of bone loss, increased Ca and vitamin D3 in plasma, improved BMD, and also prevented the inflammation and oxidative stress (improved TNF-α, CRP and MDA) compared to the positive control. The histopathological examination of treated groups showed an improvement in bone histology and protection against bone loss. However, thyme powder showed more effective impact than rosemary. Our study demonstrates that thyme and rosemary effectively mitigated calcium deficiency-induced bone loss and maybe considered as promising candidates for preventing bone resorption and osteoporosis.